Utilisation des TIC : sentiment d’efficacité personnelle des directions d’école franco-canadienne - Claire IsaBelle; François Desjardins; Freddy Bofili (Questions Vives, 2012)
If research in education has suggested that pedagogical use of ICT has had some positive effects on learners in general, it must be noted that studies have also shown that ICT use by teachers is low both in primary as well as secondary schools. One of many factors that could explain this is simply the lack of real support offered by the school principals for an effective integration of ICT in the pedagogical practice. For this support to be possible, the school principals need to have a positive perception of their own competency levels as related to technology use. This study aims to assess how French-language school principals in Canada (n=213) evaluate their own competency levels when it comes to using ICT according to four orders as mapped by a model suggested by Desjardins (2005). The data shows that the principals assess their competency levels differently depending on the type of use they make of technology and that this profile varies depending on the years of experience as principals.